2011
DOI: 10.1021/ja207385y
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of the Spirocyclic Imine Marine Toxin (−)-Gymnodimine and an Unnatural C4-Epimer

Abstract: The first total synthesis of the marine toxin (−)-gymnodimine (1) has been accomplished in a convergent manner. A highly diastereo- and enantioselective exo-Diels–Alder reaction catalyzed by a bis-oxazoline Cu(II) catalyst enabled rapid assembly of the spirocyclic core of gymnodimine. The preparation of the tetrahydrofuran fragment utilized a chiral auxiliary based anti-aldol reaction. Two major fragments, spirolactam 56 and tetrahydrofuran 55, were then coupled through an efficient Nozaki–Hiyama–Kishi reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 109 publications
1
48
0
Order By: Relevance
“…Another remarkable example of DBCE reaction is the preparation of trisubstituted tetrahydrofuran 187 c,o ne of two principal subunits of the marine algal toxin (À)-gymnodimine (Table 4), through ah ighly stereoselective iodocyclization of an acyclic alkene bearing ab is-2,6-dichlorobenzyl (DCB) ether. [5,58] Indeed, the treatment of acyclicolefin 186 a with iodine in acetonitrile at À20 8Cg ave successfully the expected product 187 a in 72 %y ield with poor selectivity (1:1 cis/trans ratio). Replacing the benzyl group at C6 by ap ivaloate slightly improvedt he cis/trans selectivity from 1:1t o3 :1 ( Table 4, entries 1a nd 2).…”
Section: Activationo Fa Nalkene Positioned G To Ab Enzyloxygroup 41mentioning
confidence: 99%
See 1 more Smart Citation
“…Another remarkable example of DBCE reaction is the preparation of trisubstituted tetrahydrofuran 187 c,o ne of two principal subunits of the marine algal toxin (À)-gymnodimine (Table 4), through ah ighly stereoselective iodocyclization of an acyclic alkene bearing ab is-2,6-dichlorobenzyl (DCB) ether. [5,58] Indeed, the treatment of acyclicolefin 186 a with iodine in acetonitrile at À20 8Cg ave successfully the expected product 187 a in 72 %y ield with poor selectivity (1:1 cis/trans ratio). Replacing the benzyl group at C6 by ap ivaloate slightly improvedt he cis/trans selectivity from 1:1t o3 :1 ( Table 4, entries 1a nd 2).…”
Section: Activationo Fa Nalkene Positioned G To Ab Enzyloxygroup 41mentioning
confidence: 99%
“…Moreover, tetrahydrofurans are found in a large number of bioactive natural products and synthetic compounds . For example, molecules such as jaspine B, (+)‐davanone, (+)‐artemone, (−)‐gymnodimine, (+)‐varitriol, trilobacin, furanodictine A and B, and ι‐ and κ‐carrageenan have shown biological properties including antiviral, antitumor, antihyperlipidemic, antioxidative, and antiinflammatory activities (Figure ). As an example, eribulin, which mimics part of the structure of the marine macrolide halichondrin B, is now in clinical trials as a promising breast anticancer agent…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a useful alternative for increasing the electrophilicity of the carbonyl carbon is represented by employment of benzenesulfonyl‐type groups (e.g., tosyl). Romo studied the addition of organometallics to δ‐lactam 52 , finding that the use of only a slight excess of n ‐BuLi gave exclusively the double addition product (i.e., alcohol 53a ) (Scheme ) 46. However, by switching to a less nucleophilic Grignard reagent (in excess) it was possible to obtain ketone 54 as the major product.…”
Section: Addition Of Organometallics To Amides: Synthesis Of Ketonesmentioning
confidence: 99%
“…156, 157 The nature of continuing challenges to synthesize those structurally complex molecules also have been discussed recently. 158, 159 A detailed pharmacological study with 109 and 110 revealed that they are ligands for a wide range of nAChRs with high potency but limited selectivity among the receptor isoforms. 160, 161 Voltage clamp recording from muscle-type (α1 2 βγδ) or neuronal (α4β2) nAChRs revealed that 109 and 110 inhibit ACh-evoked currents with IC 50 values as low as 0.5 nM, making these compounds the most potent non-peptidyl nAChR antagonists.…”
Section: Molecules That Target Neurotransmitter Receptorsmentioning
confidence: 99%